Development of a multi-agent system for dynamic sdn control - Rukkas, Kyrylo; Morozova, Anastasiia; Zaretska, Iryna; Andriichenko, Yevheniia; Chumachenko, Dmytro (Національний технічний університет "Харківський політехнічний інститут", 2026)
Relevance. Currently, the volume of transmitted information and the quality requirements for its transmission are increasing. Recently, Software-Defined Networking (SDN) technology has been gaining popularity; however, challenges arise related to the uncertainty of the SDN network state and its elements, as well as the integration of various data streams that have different quality delivery requirements. Therefore, the task of utilizing an intelligent multi-agent system (MAS) for managing SDN networks becomes relevant. The object of research is the process of managing SDN networks. The subject of the research is models and methods for managing SDN networks. The purpose of this paper is to develop a model for the interaction of intelligent agents to ensure the effective functioning of multi-agent systems (MAS) in dynamic management of SDN. Research results. Using the analytical framework of probabilistic temporal graphs, mathematical models have been developed for two options for coordinating agents in the dynamic management of SDN networks: a system with a coordinating agent and a self-regulating MAS. Based on the analysis of the obtained probabilistic temporal characteristics of various coordination options, it has been established that self-regulating MAS are advisable in situations where agents have sufficient knowledge to solve the overwhelming majority of emerging tasks, where these solutions are highly likely to be correct, the number of agents in the system is small, and there is a high probability of effective control over the decisions made.

Актуальність. На сьогоднішній день зростають обсяги інформації, що передається, та вимоги щодо якості її передачі. Останнім часом набирає популярності технологія SDN, проте виникають труднощі, пов'язані з невизначеністю стану мережі SDN та її елементів, а також інтеграцією різних потоків, які висувають різні вимоги щодо якості доставки інформації. Тому використання інтелектуальної багатоагентної системи (МАС) для управління мережами SDN є актуальною задачею. Об'єктом дослідження є процес управління SDN мережами. Предметом дослідження є моделі та методи управління SDN мережами. Мета цієї роботи – розробка моделі взаємодії інтелектуальних агентів для забезпечення ефективного функціонування МАС динамічного управління SDN. Результати дослідження. Розроблено математичні моделі з використанням аналітичного апарату імовірнісно-часових графів двох варіантів координування агентів при динамічному управлінні SDN мережами: системи з координуючим агентом і МАС, що саморегулюється. На основі аналізу отриманих імовірнісно-часових характеристик різних варіантів координування встановлено, що саморегулюючі МАС доцільно використовувати в ситуаціях, коли у агентів достатньо знань для вирішення переважної більшості завдань, що ці рішення з високою ймовірністю виявляються правильними, невелика кількість агентів в системі, а також висока ймовірність здійснення правильного контролю прийнятих рішень.
Розробка багатоагентної системи динамічного керування SDN мережами
Keywords: SDN; network; computer network management; multi-agent systems; probabilistic-temporal graphs; мережі; управління комп'ютерними мережами; багатоагентні системи; імовірнісно-часові графи